2011
DOI: 10.3324/haematol.2011.044792
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor signaling pathway in chronic lymphocytic leukemia: distinct gene expression profiles of potential pathogenic significance in specific subsets of patients

Abstract: We profiled the expression of genes associated with Toll-like receptor signaling pathways in 192 cases of chronic lymphocytic leukemia and explored potential associations with molecular features of the clonotypic B-cell receptors. ResultsChronic lymphocytic leukemia cells express all Toll-like receptors expressed by normal activated B cells, with high expression of TLR7 and CD180, intermediate expression of TLR1, TLR6, TLR10 and low expression of TLR2 and TLR9. The vast majority of adaptors, effectors and memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 50 publications
(52 reference statements)
4
69
0
9
Order By: Relevance
“…10,[15][16][17][18][19][20][21][22][23][24][25] In addition, preliminary observations in CLL, in relatively small patient series, suggest that the frequency and patterns of mutations within several genes, namely, NOTCH1, SF3B1 and TP53, may differ amongst subsets of patients carrying stereotyped BcRs, the paradigmatic example being the recently observed enrichment of SF3B1 mutations in the clinically aggressive subset #2. [26][27][28] With this in mind, we sought to systematically evaluate the mutational status of BIRC3, MYD88, NOTCH1, SF3B1 and TP53 in 565 CLL patients assigned to one of 10 major stereotyped subsets, and representing cases with varying SHM status, i.e.…”
Section: Different Spectra Of Recurrent Gene Mutations In Subsets Of mentioning
confidence: 99%
“…10,[15][16][17][18][19][20][21][22][23][24][25] In addition, preliminary observations in CLL, in relatively small patient series, suggest that the frequency and patterns of mutations within several genes, namely, NOTCH1, SF3B1 and TP53, may differ amongst subsets of patients carrying stereotyped BcRs, the paradigmatic example being the recently observed enrichment of SF3B1 mutations in the clinically aggressive subset #2. [26][27][28] With this in mind, we sought to systematically evaluate the mutational status of BIRC3, MYD88, NOTCH1, SF3B1 and TP53 in 565 CLL patients assigned to one of 10 major stereotyped subsets, and representing cases with varying SHM status, i.e.…”
Section: Different Spectra Of Recurrent Gene Mutations In Subsets Of mentioning
confidence: 99%
“…Recent studies by us (14,15) and others (16) have demonstrated that CLL patient subgroups defined by specific molecular characteristics of their clonotypic BcRs have distinct patterns of TLR pathway gene expression, function and/or tolerance. These findings indicate that specific modalities of BcR/TLR collaboration and/or regulation may eventually affect the biological behavior of the malignant clones.…”
mentioning
confidence: 99%
“…Data analysis was performed as previously reported. 21 We assigned a "High expression level" to mRNAs showing an average ΔCt≤6.6; "Intermediate expression level" to mRNAs showing an average ΔCt>6.6 and ≤9.9; "Low expression level" to mRNAs showing an average ΔCt>9.9 and ≤13.2 and "Negative expression" to mRNAs showing an average ΔCt>13.2. …”
mentioning
confidence: 99%